Primary nasal tuberculosis due to inoculation by nasal picking: a case report - Sachidananda, Ravi; Venkataramani, Nithya; Rao, Suraksha; Ishwarappagol, Pradeep; Gundappa, Vivek; Shankarnarayan, Saikiran; K., Manjunath M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Tuberculosis of the nose is a rare entity and is usually secondary to pulmonary tuberculosis. Due to its nonspecific presentation, it can be easily missed. Early diagnosis and treatment helps to prevent associated morbidity. We present a case of nasal tuberculosis in a 39-year-old male patient with the habit of nasal picking who presented with a non-healing septal ulcer. Histopathology revealed the diagnosis of tuberculosis. He did not have any evidence of pulmonary tuberculosis. A diagnosis of primary nasal tuberculosis due to inoculation by finger nail trauma was made and patient was treated with antitubercular medications. It is important to have a high index of suspicion to prevent late diagnosis and sequelae.